2017
DOI: 10.1002/aur.1902
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between executed and imagined bimanual movements in autism spectrum conditions

Abstract: Autism spectrum conditions (ASC) are characterized by social-communicative and motor coordination difficulties but in many cases also by an impaired capability to imagine movements. In this study we found that while two handed coordination in ASC can be developed as well as in typically developed persons, the development of motor imagery could still be immature in ASC, leading to difficulties in imagining, understanding as well as programming and coordinating complex movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…However, to date, only one-handed reach to grasp has been studied in ASD, and it is unclear how individuals with ASD perform bimanual reach to grasp tasks (i.e., reaching with the goal of grasping separate targets with two limbs). While no studies have investigated discrete bimanual reach to grasp in ASD, Piedimonte et al (2018) recently reported the results of a study looking at continuous bimanual drawing in adolescents and adults with autism spectrum conditions compared to control participants. Their results indicated that there was a significant coupling effect between the limbs for both the ASD and control groups when they were asked to concurrently draw a circle with one hand and a line with the other.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to date, only one-handed reach to grasp has been studied in ASD, and it is unclear how individuals with ASD perform bimanual reach to grasp tasks (i.e., reaching with the goal of grasping separate targets with two limbs). While no studies have investigated discrete bimanual reach to grasp in ASD, Piedimonte et al (2018) recently reported the results of a study looking at continuous bimanual drawing in adolescents and adults with autism spectrum conditions compared to control participants. Their results indicated that there was a significant coupling effect between the limbs for both the ASD and control groups when they were asked to concurrently draw a circle with one hand and a line with the other.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest similar bimanual coordination performance between the two groups. However, the authors also suggested that the circles-lines task may be a less demanding coordination task than reach-to-grasp since it involves mostly proximal muscles, and therefore may not be complex enough to elicit motor coordination differences (Piedimonte et al, 2018). The current study extends Piedimonte et al (2018) by looking at kinematic performance in a discrete bimanual reach to grasp task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we were able to assess the performance of both the affected hand and the unimpaired hand in a bimanual coupling task, unlike in the previous studies (Garbarini et al, 2013; Garbarini, Turella, et al, 2015), in which only one arm was assessed. To study the bimanual coupling effect, we adopted the Circles−Lines Coupling Task (Burin, Kilteni, Rabuffetti, Slater, & Pia, 2019; della Gatta et al, 2017; Garbarini et al, 2012, 2013, 2014; Garbarini, Rabuffetti, et al, 2015; Garbarini, Turella, et al, 2015; Piedimonte et al, 2018): In this common spatial task, when participants draw simultaneously incongruent shapes (i.e., a line and a circle), the line drawing generally assumes an oval or curved shape. Crucially, this effect is not detectable in the unimanual (only one hand drawing lines) and in the congruent bimanual (both hands drawing lines) movements.…”
mentioning
confidence: 99%
“…Indeed, it is still possible that the neural representation underlying the equivalence between execution and imagery may extend to the spatial characteristics of movement, but only when it originates from intended sources (i.e., pre-planned direction of movement). For example, in a similar vein to the execution of bimanual movements, there is evidence that the executed straight-line movements of one limb can become contaminated and begin to coordinate with the imagined circular movements of the unused limb (Piedimonte et al 2018 ; see also, Ramsey et al 2010 ). In this instance, the imagined movement direction may have awakened a neural representation that is correspondingly designed for the physical execution of that same movement direction (Jeannerod 1994 , 1999 ).…”
Section: Discussionmentioning
confidence: 99%